Why do Airbnb hosts discriminate? Examining the sources and manifestations of discrimination in host practice - Farmaki, Anna; Kladou, Stella (My University, 2020)
The responsible conduct of Airbnb hosts has been emphasised following recent media reports that reveal the presence of racial discrimination. Even though the platform introduced an anti-discrimination policy as a response, eliminating discrimination requires a greater understanding on the causes of discrimination occurring in P2P settings. This study responds to this research gap by examining the discriminatory practices of Airbnb hosts. Drawing from semi-structured interviews, we confirm that host practices often manifest various types of discrimination. Nonetheless, several hosts perceive the exclusion of specific groups of guests not as discriminatory but as a necessary tactic in safeguarding their property and wellbeing and a pre-requisite for a positive P2P experience. Theoretical and practical insights are derived from this study which may direct future research on the topic and inform policymakers of issues pertinent to effective platform governance.
Keywords: P2P accommodation; Airbnb; Host practice; Discrimination